How Do Age-Group Triathlon Coaches Manage Training Load? A Pilot Study - David Procida; Jocelyn Mara; Lachlan Mitchell; Naroa Etxebarria (MDPI AG, 2024)
Multidisciplinary sports like triathlons require combining training for three different sports, and it is unclear how triathlon coaches manage this. During a 10-week period, we provided four age-group triathlon coaches with summary reports of the training completed by their athletes (n = 10) in the previous week. Coaches were then asked if the information provided to them was used to inform training prescription for the following week. The information provided to coaches included relative acute training load (rATL) and training stress scores (TSSs). Weekly fluctuations in rATL of >10% (spikes) were 83% (swim), 74% (bike) and 87% (run). Coaches adapted training loads for the upcoming week in 25% of all rATLs reported, and only 5% (swim), 33% (bike) and 9% (run) of the adjusted loads avoided spikes. Consequently, there were 22 single-discipline acute training load spikes vs. 14 spikes when combining all three disciplines. Only 1.5% of training was lost to injury, mostly after a large running-based training load spike (>30%). Coaches largely overlooked the information provided in the report when prescribing exercise for the following week, and when adjusted, it failed to bring weekly load variability <10%.